Facile oxidation of flavanones to flavones using [hydroxy(tosyloxy)iodo]benzene in an ionic liquid - Muthukrishnan, Murugan; Patil, P. S.; More, Shivaji V.; Joshi, Ramesh A. (Mendeleev Communications, 2005)
A method for the oxidation of flavationes to flavones has been developed using [hydroxy(tosyloxy)iodo] benzene (HTIB) in the room-temperature ionic liquid 1,3-di-n-butylimidazolium bromide ([bbim]Br-+(-)).